Implementasi “Promoter” sebagai Strategi Pembangunan Reputasi Polri di Level Kepolisian Daerah - Novia Widiastuti; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
The police is a state institution that has functions in the field of maintaining public orderly and security, law enforcement, protection, patronage and service to communities. But along with the many negative news about the police circulating, a bad reputation about the state institution has been formed in the community. To minimize bad reputation in the Police Department, on July 13 2016 in the leadership of Drs. H.M. Tito Karnavian, M.A.Ph.D as National Police Chief, a breakthrough was launched in the form of Promoter motto (Professional, Modern, Reliable).This study aims to determine the implementation of Promoter at the regional police level as one of the Police's reputation development strategies. According to Fombrum, there are four aspects of corporate reputation that need to be addressed, namely: credibility ,trustworthiness, reliability and responsibility. This research is a qualitative research with a case study method. Data collection methods applied in this study are in-depth interviews, observation, and documentation studies. The research data was analyzed using analysis techniques by Miles and Huberman. Researcher found that the Central Java Regional Police had realized the eleven Promoter points. Even so, based on the Fombrum theory, Central Java Regional Police cannot be titled as credible because it only performs tasks and functions pre-entif while the preventive function of the community is still being complained of. In achieving internal trustworthiness, Central Java Regional Police gives appreciation to members of the Police through the Police Award, labor insurance BPJS for the welfare of the police officers and a multifunctional Promoter Card. Meanwhile, the reliability of the National Police at the Regional Police level in public eyes is still not maximal due to the lack of publications for information technology-based programs such as in the SIM, BPKP and STNK online services so there are still many people who do not know about these programs which impacts people’s assumption about the difficulty in processing these documents.